2020
DOI: 10.3390/ijms21093145
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibitory Effect of BJ-3105, a 6-Alkoxypyridin-3-ol Derivative, on Murine Colitis Is Mediated by Activating AMPK and Inhibiting NOX

Abstract: Inflammatory bowel disease (IBD) is a chronic relapsing inflammation in the gastrointestinal tract. Biological therapeutics and orally available small molecules like tofacitinib (a JAK inhibitor) have been developed to treat IBD, but half of the patients treated with these drugs fail to achieve sustained remission. In the present study, we compared the therapeutic effects of BJ-3105 (a 6-alkoxypyridin-3-ol derivative) and tofacitinib in IBD. BJ-3105 induced activation of AMP-activated protein kinase (AMPK) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It is mainly involved in regulating sugar, lipid, and energy metabolism, and studies have shown that activating AMPK inhibits inflammation and oxidative stress ( Salt and Hardie, 2017 ). In addition to maintaining cellular energy homeostasis, experiments have shown that inhibiting AMPK activity significantly increases the expression levels of the inflammatory factors TNF-α, IL-1β, and IL-6, thereby increasing inflammation damage ( Gurung et al, 2020 ). In addition, high AMPK expression levels in young cells promote the activities of factors, such as SIRT1, FOXO, and PGC-1α, thereby inhibiting NF-κB activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly involved in regulating sugar, lipid, and energy metabolism, and studies have shown that activating AMPK inhibits inflammation and oxidative stress ( Salt and Hardie, 2017 ). In addition to maintaining cellular energy homeostasis, experiments have shown that inhibiting AMPK activity significantly increases the expression levels of the inflammatory factors TNF-α, IL-1β, and IL-6, thereby increasing inflammation damage ( Gurung et al, 2020 ). In addition, high AMPK expression levels in young cells promote the activities of factors, such as SIRT1, FOXO, and PGC-1α, thereby inhibiting NF-κB activity.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation was known to reduce AMPK activity through multiple mechanisms [ 20 ]. Consistently, AMPK phosphorylation was shown to be significantly decreased in LPS-stimulated RAW 264.7 cells [ 39 , 40 , 41 ] and in the colonic tissues of DSS-induced colitis mice [ 42 ]. However, AMPK activation, which is initiated by phosphorylation, exerts anti-inflammatory activities in immune cells such as macrophages, neutrophils, T cells, and mast cells [ 26 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 95%
“…However, AMPK activation, which is initiated by phosphorylation, exerts anti-inflammatory activities in immune cells such as macrophages, neutrophils, T cells, and mast cells [ 26 , 43 , 44 ]. AMPK activator administration has been confirmed to attenuate DSS-induced colitis in mice [ 42 , 45 ]. Like previous studies [ 39 , 40 ], our results showed that AMPK phosphorylation was downregulated in macrophages in response to 1mh LPS treatment and p-AMPK level was decreased in the colonic tissues of DSS-induced mice, but AOS could induce AMPK activity in vivo and in vitro by increasing AMPK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of these two proteins might alleviate multiple pathological features such as cell growth and apoptosis by mediating the expressions of various genes in response to cell stimuli, and decelerate the degeneration of colonic inflammation. 42,43 Furthermore, the mRNA level of IL-17 in colonic tissues was also remarkably arisen in UC mice while the HDC treatment restrained this enhancement. The above results suggested that HDC might inhibit the IL-17/ JAK2/STAT3 signaling pathway which precludes the secretion of proinflammatory cytokines in UC mice.…”
Section: Discussionmentioning
confidence: 97%